Utility of 2-thioxo-pyrido[2,3-d]pyrimidinone in synthesis of pyridopyrimido[2,1-b][1,3,5]-thiadiazinones and pyridopyrimido[2,1-b][1,3]thiazinones as antimicrobial agents - Yasser H. Zaki; Sobhi M. Gomha; Amany M. G. Mohamed (Chemistry Central Journal, 2017)
Abstract Background Pyridopyrimidines are of current interest because of their extensive variety of biological and pharmacological activities. Results A series of pyrido[2′,3′:4,5]pyrimido[2,1-b][1,3,5]thiadiazinones was obtained by aminomethylation of pyridopyrimidinethione with formaldehyde solution (37%) and different primary aromatic amines. Another series of pyrido[2′,3:4,5]pyrimido[2,1-b][1,3]thiazinones was prepared by Michael addition reaction of pyridopyrimidinethione to the activated double bond of a number of arylidene malononitrile and 2-(benzo[d][1,3]dioxol-5-ylmethylene)malononitrile. The mechanisms of formation of the synthesized compounds were discussed and the assigned structure was established via microanalysis and spectral data (IR, 1H NMR, and Ms.). A comparative study of the biological activity of the synthesized compounds with chloramphenicol and trimethoprim/sulphamethoxazole is shown in Table 1. Generally, all synthesized compounds showed adequate inhibitory effects on the growth of Gram-positive and Gram-negative bacteria. Conclusions In this study, we use a simple (synthetic) strategy for the synthesis of pyrimidothiadiazines, based on their aminomethylation through the Mannich reaction; they have also been synthesized by the application of the Michael addition to activated nitriles. Mechanisms and structures of the newly synthesized compounds were examined: the antimicrobial activity of some selected compounds was evaluated, which demonstrated adequate inhibitory effects. Graphical abstract The strategic structures of the products (7a–g).